Synthesis, characterization and bioactivity Study from azo – ligand derived frommethyl-2-amino benzoatewith some metal ions - Israa H. Ibraheem; Noora Saad Mubder; Mays Mohammed Abdullah; Haider Al-Neshmi (مجلة بغداد للعلوم)
A Ligand (ECA) methyl 2-((1-cyano-2-ethoxy-2-oxoethyl)diazenyl)benzoate with metals of (Co2+, Ni2+, Cu2+) were prepared and characterization using H-NMR, atomic absorption spectroscopy, ultra violet (UV) visible, magnetic moments measurements, bioactivity, and Molar conductivity measurements in soluble ethanol. Complexes have been prepared using a general formula which was suggested as [M (ECA)2] Cl2, where M = (Cobalt(II), Nickel(II) and Copper(II), the geometry shape of the complexes is octahedral.